Fragments of a Seminar on Virtueand Autonomy - Castoriadis, Cornelius (1999)
After having underlined the three difficulties of the Aristotelian detinition of virtue-the oximoron hexis proairetike as central paradox, the difticult balance between phrorimos and logos, and the enigmatic impression of that "regarding us" in relation to which everything is at stake- the A.shows that his explanation also gives all its sense to the autonomy project that is at the heart of his work. This project, as any other philosophical project, could not begrounded nor justitied a priori. Nevertheless, it is the only one that opens human liberty to its true dimension, namely, the position /acceptance of new forms. This does not exempt one from examining its internal coherence nor of looking for its real bearers in society.